2023
DOI: 10.1088/1748-9326/aca9e6
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of diurnal smoothing for grid integration of wind power

Abstract: Smoothing of generation variability, i.e., reduction of variance in the aggregate generation is crucial for grid integration of large-scale wind power plants. Prior studies of smoothing have focused on geographical smoothing, based on distance. In contrast, we propose a novel concept “diurnal smoothing” that depends on spatial variations in the timing of seasonal-mean diurnal cycle peak. Considering the case of India, which experiences a strong diurnal cycle of wind-speed, we show how spatial heterogeneity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The co-variability of generation with demand for electrical energy is another dynamic factor not considered here, and other work has noted how the anti-phasing between wind generation and air temperatures in India contributes to enhanced variability in electricity demand net of wind generation on intra-seasonal timescales [83]. However, other studies have suggested possible compensatory generation from solar PV on diurnal [84] and seasonal timescales [33], with the phasing of the annual cycle of wind and solar PV generation particularly advantageous in the South of India [85]. Further investigation of potential balancing between these two sources is warranted, given the importance of wind and solar PV technologies within India's national renewable targets.…”
Section: Discussionmentioning
confidence: 97%
“…The co-variability of generation with demand for electrical energy is another dynamic factor not considered here, and other work has noted how the anti-phasing between wind generation and air temperatures in India contributes to enhanced variability in electricity demand net of wind generation on intra-seasonal timescales [83]. However, other studies have suggested possible compensatory generation from solar PV on diurnal [84] and seasonal timescales [33], with the phasing of the annual cycle of wind and solar PV generation particularly advantageous in the South of India [85]. Further investigation of potential balancing between these two sources is warranted, given the importance of wind and solar PV technologies within India's national renewable targets.…”
Section: Discussionmentioning
confidence: 97%
“…Another innovative approach involves co-locating offshore wind and wave power to mitigate variability in individual renewable energy sources 26 . The role of diurnal smoothing, influenced by spatial variations in wind speed timing, has also been explored 27 . Moreover, there are several proposals for producing hydrogen as an ancillary service to address offshore wind power variability and facilitate further expansion both from researchers 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%